Testing the reflection assumption: A comparison of eyewitness ecology in the laboratory and criminal cases. (July 2018) - Flowe, Heather D; Carline, Anna; Karoğlu, Nilda
In the US, experts are often called upon to provide evidence during criminal trials regarding eyewitness identification research. A key factor is probative value: to what extent are findings from laboratory studies generalisable to the real world? In order to answer this question, this article explores the issue of eyewitness ecology, a term referring to the environmental context in which people witness crimes, which includes characteristics of perpetrators and the viewing conditions, as well as the identification context. Specifically, we explore the extent to which the typical eyewitness ecology found in laboratory studies reflects or is similar to real-world conditions. We coded the characteristics of the published literature on criminal identification in the laboratory ( n = 309), and the results were compared to the characteristics of a stratified random sample of felony cases ( n = 721) obtained from a large metropolitan district in the United States. This analysis demonstrated that in the criminal cases compared to the laboratory studies, duration of exposure to the culprit and retention interval length were significantly longer, and weapons, violence and showup identifications were more prevalent. Additionally, the laboratory studies and criminal cases differed with respect to participant/witness race. These findings indicate a need to broaden the range of conditions employed in the laboratory to increase the applicability of eyewitness identification research to the legal system.